Therapeutic successes obtained through pharmaceutical services aimed at the patient, family and community - Melo, Renato Bruno Cavalcante de (2022)
Objective: to prepare an integrative review pharmaceutical services provided to the patient, family and community in Brazil. Methods: refers to bibliographic verification and database consultation about pharmaceutical services. Results: it was detected that numerous categories of services conceived in the context are exposed and positively appreciated in the use process and the therapeutic consequences for the user. The services provided by pharmacists, such as pharmacotherapeutic monitoring, medication reconciliation, health screening, management of self-limited health problems and others, which are essential for the rational use of medicines and care / safety attributed to patients Conclusion: shows greater recognition of the professional's skills in the health care system, promoting the enhancement of the impact of their performance on improving pharmacotherapy, improving health outcomes, preventing diseases and in the health rise of the population.